2007
DOI: 10.1167/iovs.06-1020
|View full text |Cite
|
Sign up to set email alerts
|

Polylactic Acid for Visualizing the Vitreous Body during Vitrectomy

Abstract: PLA can be a new surgical adjuvant to visualize the vitreous body during vitrectomy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2009
2009
2013
2013

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…In their reports, 11-deoxycortisol could visualize the vitreous as clearly as TA, with no adverse events such as IOP rise or corneal endothelial damage. Yamashita et al demonstrated polylactic acid for this purpose [117]. Polylactic acid is a biodegradable substance without any biological effects.…”
Section: Adverse Eventsmentioning
confidence: 99%
See 1 more Smart Citation
“…In their reports, 11-deoxycortisol could visualize the vitreous as clearly as TA, with no adverse events such as IOP rise or corneal endothelial damage. Yamashita et al demonstrated polylactic acid for this purpose [117]. Polylactic acid is a biodegradable substance without any biological effects.…”
Section: Adverse Eventsmentioning
confidence: 99%
“…At the same time, PLA has been used in orthopedic surgery and has been reported to be safe [118]. PLA granules are originally white and adhere to the gel-like structure so easily that they assist in visualizing the transparent vitreous as do TA granules, but with no harmful consequences in rabbits and subhuman primates [117]. These two agents might be good alternatives if TA is proven to be intolerably harmful in the future.…”
Section: Adverse Eventsmentioning
confidence: 99%
“…Diffuse residual vitreous cortex after surgical PVD was reported to be much more frequent in diabetic retinopathy than in other diseases,1114 and TA was essential to observe it. On the other hand, an “island-like” residual vitreous cortex, termed premacular residual vitreous cortex, frequently was found to be left on the macula after PVD in non-diabetic eyes 12,13,20. The premacular residual vitreous cortex can provide a good scaffold for cell proliferation and extracellular matrix production, resulting in future macular pucker and epiretinal membranes 21.…”
Section: Discussionmentioning
confidence: 99%
“…In that study, upregulation of retinal GFAP, an indicator of vitrectomy-related retinal trauma, was also detected in vitrectomy-treated rabbit eyes. The majority of recent studies on retinal function following vitrectomy have been short-term toxicity or clearance experiments (3739). Intravitreal injection of PBS, bacterial media, or vancomycin alone can cause a transient posterior segment inflammation that, in the rabbit eye, resolves within 4 h (data not shown).…”
Section: Discussionmentioning
confidence: 99%